Virtual environment for training auditors with information security - Fediushyn, O. I.; Yatsiuk, O. O.; Rusanov, H. O. (ВА ЗС АР; НТУ "ХПІ"; НАУ, ДП "ПДПРОНДІАВІАПРОМ"; УмЖ, 2021)
The goal of the study is to create a laboratory infrastructure that allows instructors to quickly create virtualized environments for simulating various cyber threats. The testing environment for this demo consists of Windows 10, Ubuntu 16.4, Kali linux and OSSIM. Completed attacks together with potential moves are gathered and put into various attack tree diagrams for analysis so as to find out the most effective attacks against each host.
Keywords: cybersecurity; virtual machines; cyber threats; SIEM; vulnerabilities